ORGANIZATIONAL AGILITY (STUDY OF HANDLING OF POST HOUSEHOLD VIOLENCE IN PEKANBARU CITY): AGILITY ORGANISASI (STUDI PENANGANAN PASCA KEKERASAN DALAM RUMAH TANGGA DI KOTA PEKANBARU) - Indah Indah Febriansyah Nasution; Adianto (SOSIOEDUKASI, 2023)
Population growth and the development of Pekanbaru City can affect the level of violence against women and children. One of them is Domestic Violence (KDRT). The agility of public organizations is very influential for fast handling and the right time for solving domestic violence cases, in Pekanbaru City the public organization that handles cases is the Technical Implementation Unit for the Protection of Women and Children (UPT PPA). This study aims to describe and analyze agility as well as identify and analyze factors that hinder UPT PPA's agility in dealing with the aftermath of domestic violence in Pekanbaru City. This study uses the theory of Zhang and Sharifi in Sri Raharso (2018) which uses indicators: Responsiveness, Competency, Flexibility, Quickness. The research method used is a qualitative method with a case study approach and is descriptive in nature. The results found that UPT PPA's agility in handling post-domestic violence was still not good and there were several factors that hindered UPT PPA's agility in handling post-domestic violence in Pekanbaru City.